The ideological meaning of primary education in Turkish modernization - Şahin, Alper. (Thesis (Ph.D.)-Bogazici University. Institute for Graduate Studies in Social Sciences, 2002., 2002)
In this thesis, it was intended to find out the influence of modernization and socioeconomic politics of the State on the politics of primary education. The aim of the study is to discover the citizen model that the modem Turkish State wanted to create. The researcher used a historical perspective to understand the the features of modem primary education policies in Turkey. Therefore three primary school civics textbooks are examined from 1928, 1934 and 1937. By this way the difference between citizenship understanding during various periods is understood. Hermeneutics and content analysis methods are used to examine the textbooks. The results demonstrated that the education is an important aspect of creating a modem citizen. The nationalism has also important place in the modernization movement. Nevertheless the emphasis on freedom changes its intensity throughout the years from individual freedom to freedom of the country. The State control over public is clearly observable in the textbooks which leaves a small room for self expression. The content of the civics textbooks aim to shape the future citizen with the following characteristics: nationalist, able to self-govern with limited freedom, gaining strenght with mutual responsability and solidarity and one who values education.
Keywords: Education, Elementary -- Turkey.; Education, Primary.